Derrida, time, and infinite finitude: weakening Hägglund's negative - MacLachlan, I (Philosophy Documentation Center, 2018)
This article presents a critique of the influential reading of Derrida proposed by Martin Hägglund, focusing in particular on the latter’s account of time, différance, and finitude in Derrida’s work. It concludes that, at root, there is a persistent misapplication of a notion of the negative in Hägglund’s reading, and that this feature can most revealingly be linked to a misconception about Derrida’s conception of mortal limits.